Subjek, Kuasa, dan Wacana Love Myself: Pidato BTS dalam Perspektif Michel Foucault - Maharani Putri, Ainunisa (Program Studi Magister Linguistik Terapan UNJ, 2025)
This article analyzes the speech of Korean pop idol BTS titled “Love Myself” at the United Nations (UN) forum in 2018 during the UN General Assembly (UNGA) in collaboration with UNICEF. This research was conducted with a focus on the concepts of subject, power, and discourse. The purpose of this research is to reveal how the concepts of language and discourse are used to shape and maintain social reality in the context of popular culture and mental health. This research uses a descriptive qualitative method to describe the practices of meaning, identity construction, and power operations in language. The data is analyzed through critical reading of the text of the speech delivered by Kim Namjoon or RM as a representative of BTS. The theory used in this research is Foucault's discourse analysis with a linguistic turn approach in cultural studies. The results found that the speech delivered by BTS functions as a resistance discourse that defines the subject through self-love narratives, and intervenes in the dominant power structure by reframing the meaning of identity. This research contributes to cultural studies by showing how popular discourse can be an arena for the articulation of power and subjectivity, and opens up new space for discourse analysis in the context of celebrity activism. This research also fills a gap in discourse studies by presenting a critical analysis of the practice of self- representation in contemporary culture that has not been widely explored theoretically.